Vitamin D Insufficiency and Epistemic Humility: An Endocrine Society Guideline Communication - McCartney, Christopher R; McDonnell, Marie E; Corrigan, Maureen D; Lash, Robert W (The journal of clinical endocrinology and metabolism, 2024)
Abstract A long-held precept is that vitamin D supplementation primarily, if not exclusively, benefits individuals with low circulating 25-hydroxyvitamin D (25[OH]D) concentrations at baseline. However, the most appropriate 25(OH)D threshold to distinguish unacceptably low vs reliably adequate concentrations remains controversial. Such threshold proposals have largely been based on observational studies, which provide less robust evidence compared to randomized clinical trials (RCTs). Since the Endocrine Society's first vitamin D–related guideline was published in 2011, several large vitamin D–related RCTs have been published, and a newly commissioned guideline development panel (GDP) prioritized 4 clinical questions related to the benefits and harms of vitamin D supplementation in generally healthy individuals with 25(OH)D levels below a threshold. The GDP determined that available clinical trial evidence does not permit the establishment of 25(OH)D thresholds that specifically predict meaningful benefit with vitamin D supplementation. The panel noted important limitations in the available evidence, and the panel's overall certainty in the available evidence was very low. Nonetheless, based on the GDP's analyses and judgments, the Endocrine Society no longer endorses its previously proposed definition of vitamin D “sufficiency” (ie, at least 30 ng/mL [75 nmol/L]) or its previously proposed definition of vitamin D “insufficiency” (ie, greater than 20 ng/mL [50 nmol/L] but lower than 30 ng/mL [75 nmol/L]). The Endocrine Society's rationale for such is the subject of this Guideline Communication.